Avengers : 4-movie collection [videorecording (Blu-Ray)]. - Downey, Robert, Jr., 1965-; Evans, Chris, 1981-; Ruffalo, Mark; Hemsworth, Chris; Cumberbatch, Benedict, 1976-; Johansson, Scarlett, 1984-; Renner, Jeremy; Cheadle, Don; Rudd, Paul; Larson, Brie, 1989-; Gillan, Karen, 1987-; Gurira, Danai; et al.
The Avengers: Nick Fury of S.H.I.E.L.D. brings together a team of superhumans to form The Avengers to help save the Earth from Loki and his army.